Case Report: Therapeutic effect of efgartigimod in refractory anti-GQ1b antibody syndrome coexisting with myasthenia gravis - Watanabe, Keiko; Takahashi, Seiya; Kanda, Akane; Watanabe, Takuya; Kakinuma, Yuki; Yano, Satoshi; Kinno, Ryuta (Frontiers in Immunology, 2025)
Anti-GQ1b antibody syndrome is a spectrum of autoimmune neurological disorders that includes Miller Fisher syndrome, Guillain-Barré syndrome (GBS) with ophthalmoplegia, Bickerstaff brainstem encephalitis, and acute ophthalmoplegia without ataxia. These conditions are characterized by the presence of immunoglobulin G (IgG) antibodies targeting GQ1b gangliosides. The coexistence of anti-GQ1b antibody syndrome and myasthenia gravis (MG) is rare and presents diagnostic and therapeutic challenges. We report the case of an 84-year-old Japanese man with overlapping features of both disorders, describing his clinical course and response to add-on treatment with the neonatal Fc receptor antagonist efgartigimod. He presented with fever and diarrhea, followed by acute limb weakness. He was initially suspected of having had a stroke but was later diagnosed with GBS based on areflexia, anti-ganglioside antibody positivity, and nerve conduction abnormalities. Intravenous immunoglobulin therapy was initiated but his condition worsened, leading to respiratory failure and mechanical ventilation. Subsequently, bilateral ptosis and eye movement dysfunction emerged, prompting the consideration of MG. Anti-acetylcholine receptor antibodies and tensilon test results were positive and high-dose methylprednisolone was administered, resulting in partial improvement. Plasmapheresis was performed, but profound limb weakness and respiratory failure persisted; intravenous efgartigimod was thus introduced. Remarkably, the patient’s respiratory function improved within 7 days, leading to ventilator weaning, and his limb weakness showed notable recovery. After a second cycle of efgartigimod, the patient regained speech and independent mobility, allowing transfer to a rehabilitation facility. His case underscores the diagnostic complexity of overlapping anti-GQ1b antibody syndrome and MG, and it highlights the therapeutic potential of efgartigimod in treating refractory cases of overlapping autoimmune neuromuscular syndromes. Given the rapid efficacy of efgartigimod for improving both respiratory and motor functions in this case, it is apparent that efgartigimod can be a valuable therapeutic option in complex neuromuscular autoimmune conditions.